Risk factors associated with wheezing in infants - Lillian S.L. Moraes; Olga A. Takano; Javier Mallol; Dirceu Solé (Brazilian Society of Pediatrics, 2013)
Objective: to identify possible risk factors associated with wheezing in infants (12-15 months-old) in the state of Mato Grosso, Brazil. Methods: this was a cross-sectional study performed by applying a standardized written questionnaire from the international study on wheezing in infants (Estudio Internacional de Sibilancia en Lactantes - EISL), phase 3. Parents and/or guardians of infants were interviewed at primary health care clinics or at home from August of 2009 to November of 2010. Factors associated to wheezing were studied using bivariate and multivariate analysis (using the Statistical Package for Social Sciences [SPSS] v.18.0), and expressed as odds ratios (OR) and 95% confidence intervals (95% CI). Results: the written questionnaire was answered by 1,060 parents and/or guardians. The risk factors for wheezing were: history of asthma in the family [mother (OR = 1.62; 95% CI = 1.07-2.43); father (OR = 1.98; 95% CI = 1.22-3.23); siblings (OR = 2.13; 95% CI = 1.18-3.87)]; history of previous pneumonia (OR = 10.80; 95% CI = 4.52-25.77); having had more than six upper respiratory tract infections (URTIs) (OR = 2.95; 95% CI = 2.11-4.14); having had first URTI before the third month of life (OR = 1.50; 95% CI = 1.04-2.17); living in a moderately polluted area (OR = 1.59; 95% CI = 1.08-2.33); paracetamol use for URTI (OR = 2.13; 95% CI = 1.54-2.95); and antibiotic use for skin infection (OR = 2.29; 95% CI = 1.18-4.46). Conclusions: the study of risk factors for wheezing in the first year of life is important to help physicians identify young children at high risk of developing asthma and to improve public health prevention strategies in order to reduce the morbidity of wheezing in childhood.